Hasta que se respire libertad - Hernández, Alejandra Fabiana; Piturro, Sabrina; Maldonado, Sol Malena; Nuñez Romero, Zoe Naomi Maitena; Leone, Victoria Zarina; López Britos, Paula; Suárez, Carla Melina; Larracochea, María Guadalupe; Villareal, Cintia Ruth; Ortiz, Letizia; Carabajal, Ana; Boiero, Melina; et al. (Cátedra de Grabado I. Departamento de Artes Visuales. Facultad de Artes, UNC, 2024)
Equipo de cátedra: Prof. Alejandra Hernández, Prof. Lucía Alvarez Pérez, Prof. Nadine Madelón, Prof. Laura Lucero, Prof. Belén Canesini, Prof. Ignacio Font.